Implementation of Non-Cash Financial Transactions as a Payment System for Non-Civil Servant Employee Service Expenditures at the Cilegon City Regional Secretariat - Ahyarani Karimah; Ika Utami Widyaningsih; Firli Agusetiawan Shavab; Titis Nistia Sari; Hayati Nupus (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2023)
Non-cash Financial Transactions began to be carried out gradually in the Cilegon City Government in 2018 with the issuance of Cilegon Mayor Regulation Number 20 of 2018 concerning Online Disbursement Orders and Implementation of Non-cash Transactions in the Cilegon City Area. This study aims to find out the procedure for the payment and the constraint in the process of Non-cash Transaction disbursement in the spending of personnel service expenditure of Non-civil Servant in the Cilegon City Regional Secretariat. The researchers used a descriptive qualitative method. The data were collected using triangulation. Triangulation is a process of gathering several techniques of taking existing data sources. In this study, the data were obtained using observation, interview, library research, and documentation. The result of this study shows the procedure of implementation of Non-cash financial transactions as a service payment system for Non-civil Servant employees in Cilegon City Regional Secretariat runs quite effectively through some aspects namely, fast, easy, accurate, and safe.